Analytics Culture and Absorptive Capacity as Mediators of Big ‎Data Value Creation in SMEs - Prasad , Yanamadala Durga; Sonker , Dr Sumit Singh (International Journal of Basic and Applied Sciences, 2025)
This paper examines the ways small and medium firms derive value from big data analytics. It notes that many firms invest in analytics ‎technology. Yet many struggle to turn data into strategic value. The research asks whether analytics culture and absorptive capacity help. ‎Analytics culture involves using data in daily decisions. Absorptive capacity involves finding, learning, and using outside knowledge. The ‎model tests human and technological analytics capabilities. It tests analytics culture and absorptive capacity as mediators. The results show ‎that both mediators matter. Analytics culture amplifies the effect of capabilities on business value. Absorptive capacity strengthens this effect. ‎Together, these factors help firms translate analytics investments into measurable outcomes. The findings add new empirical evidence for ‎SMEs. Results show that technology alone is not enough. Firms need culture and learning routines. Managers should develop analytics ‎mindsets and promote knowledge sharing and external learning. These steps help align analytics with organizational goals and results. The ‎model demonstrated strong fit and predictive accuracy. The mediators partly explain the process through which capabilities lead to value. ‎The research provides clear recommendations for managers in SMEs. Leaders should align technology, people, and processes. Training and ‎hiring matter. Leaders should reward knowledge sharing. Firms should develop routines to learn from partners. The research adds to theory ‎and practice. Limitations include the single-country, cross-sectional design. Future work should use other countries and longitudinal data‎.